Comparative Study of Commercial Bread Wheat Varieties and Advance Wheat Lines to Explore Superior Attributes for Variety Development and Future Breeding Guidelines - Fatima, Eman; Ali, Hazib; Muhammad Faisal; Muhammad Waseem; Khurram, Fajar; Usman, Zunaira; Muhammad Loqman; Ali, Mohsin; Mehmood Ul Hassan; Iqbal, Arshad (Indus Journal of Bioscience Research, 2024)
Knowledge about the potential and performance of advance wheat lines and commercial bread wheat varieties are vital for implicit variety adaptation. Comparative study was designed to quantify the performance of advance wheat lines, sixteen commercial wheat varieties and fourteen advance wheat lines were tested in randomized complete block design with 3 replications at Agricultural Research Station Baffa, Mansehra during wheat growing season 2022-23. The study evaluated wheat advance lines yield and resistance against powdery mildew disease, as compared to commercial varieties for adaptability and variety development. Days to 50% heading, plant height (cm), grain yield (kgha-1), disease scoring and % severity of disease data was subjected to analysis of variance using statistical software R. Analysis of variance revealed significant differences for all parameters. Advance wheat lines identified for early heading were PR-115 (131) and PR-106 (132). Similarly, commercial variety Hashim-2010 (133) showed early heading. Commercial wheat varieties PS2013 (95.6cm), Janbaz (96cm), PS2005 (96.6cm) and advance wheat lines PR106 (95.6cm), PR115 (95.6cm), IBGE (96.6cm) were found semi dwarf. Grain yield of commercial wheat variety Janbaz 6566.6 (kgha-1) was at par with advance wheat line PR118 6500(kgha-1). Commercial bread wheat varieties (PK2015, PS2005) and an advance line (PR115) showed lowest severity (2%) to powdery mildew disease. An advance line (PR115) and four commercial bread wheat varieties (PS-2005, PS-2008, PK-2015, Faisalabad-2008) were found resistant against powdery mildew disease. Commercial bread wheat varieties PS-2005, PS-2008, PK-2015, Faisalabad-2008 and advance wheat line PR115 can be utilized as resistant source of powdery mildew in future breeding programs